EKSISTENSI ASAS KESEIMBANGAN DALAM KONTRAK KERJA SAMA PENANAMAN MODAL - Kadek Septia Ningsih; A A Gede Agung Dharmakusuma; Desak Putu Dewi Kasih (Kertha Negara : Journal Ilmu Hukum, 2013)
In succeeding national development program in Indonesia, one effortperformed by the Government is by providing opportunity for foreigninvestors to invest in Indonesia. Besides using other efforts such as the useof foreign assistances, the existence of corporation in building businesses isbadly needed for the sake of the business performance such as in the formof foreign investment in which the development of corporation betweenforeign parties and both government and private sectors in Indonesia isvery important in particular with transferring technology and skill.